Monomer for thermal crosslinking type high-temperature-resistant polyimide film material, polyimide film material and preparation method of polyimide film material

By introducing vinyl and pyrimidine structures into polyimide materials, the heat-crosslinked polyimide film is solved, and the thermal performance of polyimide films in the prior art is achieved, and high temperature stability and simplification are achieved Preparation process, suitable for flexible OLED substrates.

CN119143681APending Publication Date: 2024-12-17TIANJIN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411293021.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The thermal performance of the existing polyimide films cannot meet the performance requirements of flexible OLED substrates, and the existing cross-linking methods are complex or require heavy equipment, which limits its application in the field of flexible display.

Method used

Introduce vinyl as a crosslinkable group and a pyrimidine structure in polyimide materials, form a three-dimensional network structure through thermal crosslinking, combine with large volume side groups, design new diamine monomers and prepare heat crosslinking through a simple high-temperature process Linked polyimide film.

Benefits of technology

It significantly improves the thermodynamic properties of the polyimide film, with the decomposition temperature reaching 500-524℃ at high temperature and the glass transition temperature between 274-295℃, which meets the high temperature resistance requirements of flexible substrates, and simplifies the preparation process, avoiding heavy use. Equipment and color-deep chemical crosslinking agent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143681A_ABST
    Figure CN119143681A_ABST
Patent Text Reader

Abstract

The invention relates to a monomer for a thermal crosslinking type high-temperature-resistant polyimide film material, the polyimide film material and a preparation method of the polyimide film material. The diamine monomer is 6-(2, 3, 5, 6-tetrafluoro-4-vinyl phenoxy) pyrimidine-2, 4-diamine, and the solvent is a solvent. The preparation method comprises the following steps: copolymerizing a monomer with other diamine monomers and dianhydride monomers to prepare polyimide, introducing a tetrafluorostyrene structure on a polyimide main chain, and thus preparing the thermal crosslinking type high-temperature-resistant polyimide film. Through thermal crosslinking of vinyl and large-volume side groups, polyimide is endowed with the advantage of high temperature resistance and improvement of mechanical properties. According to the polyimide film material prepared by the invention, the temperature of 5% of mass loss at high temperature obtained by a thermogravimetric analyzer is 500-524 DEG C, the glass-transition temperature obtained by testing of a differential scanning calorimeter is 274-295 DEG C, and the technical requirements of a flexible substrate on a high-temperature-resistant PI material can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of high-performance polymers, and specifically relates to a thermally cross-linked high-temperature resistant polyimide material and the synthesis and performance of its thermally cross-linked film. The thermally cross-linked polyimide film has a very high decomposition temperature and excellent mechanical properties at high temperatures, and is therefore expected to be applied in the field of flexible electronic displays. Specifically, it relates to monomers for thermally cross-linked high-temperature resistant polyimide film materials, polyimide film materials, and preparation methods. Background Art

[0002] Polyimide (PI) is composed of imide ring repeating units and a rigid polymer main chain, and has excellent dimensional stability, good chemical stability and thermodynamic properties. This is due to the rigid conjugated chain structure and strong interactions between chains brought about by a large number of aromatic heterocycles and polar groups in the molecular structure. PI is widely used in high-tech fields such as microelectronics, aerospace, and national defense due to its excellent optical properties, high and low temperature resistance, and good dimensional stability.

[0003] PI film is one of the development targets of flexible substrate technology. In fact, flexible substrate technology as a support and flexible cover technology as a protector are key threshold technologies in the field of foldable displays. When used as a flexible substrate material, the glass transition temperature (T g ) and thermal weight loss temperature are two critical heat resistance parameters in practical applications. However, the thermal properties of commercially available PI films cannot meet the performance requirements of flexible OLED substrates. For example, in most relevant literature, the T of flexible PI materials with high heat resistance produced at the laboratory level is g Mainly maintained at around 250℃, T d Keep it at around 490℃, therefore, increase T g and T d It is the research focus of PI substrate materials. Introducing new monomers, stretching films, and doping inorganic materials are the key to improving PI film T g and T d However, the stretching process is not suitable for flexible OLED manufacturing, and doping with inorganic materials can only improve polymer properties to a limited extent. The key to producing high-performance PI films lies in the design and introduction of new monomers to achieve inherent high T g and T d Among the strategies to introduce new monomers, incorporating cross-linkable groups is a promising approach because it allows PI to be cross-linked into a more stable structure, thus enabling it to withstand higher processing temperatures.

[0004] Crosslinking is an emerging polymer modification method and is widely considered to be a way to improve the resistance and permeability selectivity of PI film materials. Due to the diversity of PI structures, it is easy to introduce other functional groups into its molecular structure through crosslinking reactions. Common crosslinking methods include chemical crosslinking, ultraviolet radiation crosslinking, and thermal crosslinking. In previous works, many crosslinking was performed in the PI structure to greatly improve the thermal properties of PI. For example, Guo et al. (Guo, K.; et al. Preparation and Characterization of Fluorine-containing Benzimidazole Polyimide Films with a Micro-branched Crosslink Structure. Eur. Polym. J. 2023, 205, 112723) prepared a series of fluorinated benzimidazole PI films with micro-branched crosslink structures. The crosslinked structure makes the weight loss temperature (T d5% ) is higher than 530℃, indicating its excellent thermal stability, but the film is brittle and is not suitable for application in flexible display electronic devices. Jeong et al. (Jeong, K.; et al. Effects of Crosslinking Agents on the Physical Properties of Polyimide / Amino-functionalized Graphene Oxide Hybrid Films. Polym. Int. 2018, 67(5), 588-597.) studied the effect of crosslinking agents on PI films. They modified the surface with 4-aminobenzylamine to enhance the thermal stability of PI films. T of PI / M50 d It is 472℃, which is higher than 446℃ of the original PI film, but the addition of chemical crosslinkers will change other properties of the film. For example, the optical properties will be reduced due to the color of the crosslinker itself, which is not suitable for application in the flexible industry. Jiang et al. (Jiang, S.; et al. Construction of Novel Cu-α-Diimide Interactions for Enhancing Thermal Resistance and Dimensional Stability of Polyimide Films. J. Mater. Res. Technol. 2023, 25, 1920-1930.) added α-diamine units to the BPDA-ODA framework to prepare PI-Cu composite films, and successfully formed a cross-linked network by constructing coordination bonds. The heat resistance of the PI film is enhanced, and the T of a typical PI-Cu100 film is 2.34 W / m. gis 253℃ (while the T g 202°C), but the disadvantage is that complex pressure equipment is required to prepare PI structures containing metal coordination. These studies have shown that the introduction of cross-linkable groups into PI is beneficial to improving the thermal properties of PI, but the characterization index of heat resistance has not yet been raised to the application range close to that of flexible substrate materials, and there are too complicated synthesis processes in the preparation process or heavy equipment is used in the cross-linking process. It is also necessary to design applicable monomer molecular structures containing cross-linking groups, and to further improve the heat resistance of PI materials by thermally cross-linking the molecules through a relatively simple high-temperature process. Summary of the invention

[0005] The purpose of the present invention is to provide a thermally cross-linkable high-temperature resistant polyimide material and the synthesis and performance of its thermally cross-linked film. The present invention introduces vinyl as a cross-linkable group in the PI chain to form a three-dimensional network structure at high temperature, greatly improving the thermodynamic properties, and the introduction of a nitrogen-containing heterocyclic pyrimidine structure can enhance the intermolecular force of PI and thus improve the heat resistance. In addition, the introduction of bulky side groups and multiple fluorine atoms can also give PI good optical properties. It has become an operational strategy to obtain high-performance PI by simultaneously introducing a cross-linkable structure and a bulky side group in the molecular chain. PI, as a polymer, is formed by the condensation polymerization of diamine monomers and dianhydride monomers. Therefore, according to the above strategy, the present invention has developed a new diamine monomer, and prepared a thermally cross-linked high-temperature resistant polyimide film accordingly.

[0006] The technical solution of the present invention is as follows:

[0007] The present invention provides a monomer for a heat-crosslinked high-temperature resistant polyimide film material; a diamine monomer 6-(2,3,5,6-tetrafluoro-4-vinylphenoxy)pyrimidine-2,4-diamine, whose structural formula is as follows:

[0008]

[0009] The preparation method of the diamine monomer 6-(2,3,5,6-tetrafluoro-4-vinylphenoxy)pyrimidine-2,4-diamine is as follows:

[0010]

[0011] Under nitrogen protection and in the presence of a catalyst and a polar solvent, 2,6-diaminopyrimidine-4-ol and 2,3,4,5,6-pentafluorostyrene undergo a nucleophilic substitution reaction, and then the diamine monomer 6-(2,3,5,6-tetrafluoro-4-vinylphenoxy)pyrimidine-2,4-diamine is obtained after filtration, extraction, reduced pressure distillation to remove the solvent, silica gel column chromatography purification, and drying.

[0012] The invention discloses a method for preparing a diamine monomer 6-(2,3,5,6-tetrafluoro-4-vinylphenoxy)pyrimidine-2,4-diamine. The catalysts used are calcium hydride and cesium fluoride. The molar feed amount of the raw materials is 6-(2,3,5,6-tetrafluoro-4-vinylphenoxy)pyrimidine-2,4-diamine: (2,3,4,5,6-pentafluorostyrene): (calcium hydride): (cesium fluoride) = 1:2:0.1:1.2 to 1:2:0.3:2.

[0013] The polar solvent is N,N-dimethylacetamide, and the amount of the added solvent is 5 to 10 times the total mass of the feed; the nucleophilic substitution reaction occurs at 75 to 100° C. and the reaction lasts 18 to 36 hours.

[0014] The heat-crosslinked high-temperature resistant polyimide film material prepared by using the above-mentioned monomer of the present invention is a polymer obtained by copolymerization of two diamine monomers 4,4'-diaminodiphenyl ether and 6-(2,3,5,6-tetrafluoro-4-vinylphenoxy)pyrimidine-2,4-diamine and a dianhydride monomer 4,4'-(hexafluoroisopropylene) diphthalic anhydride, and has the following reaction formula:

[0015]

[0016]

[0017] In the structural formula, m is the molar amount of 4,4'-diaminodiphenyl ether added during the copolymerization process, and n is the molar amount of 6-(2,3,5,6-tetrafluoro-4-vinylphenoxy)pyrimidine-2,4-diamine added during the copolymerization process, wherein n is 0.5 to 1.5; the characteristic is that m+n=10, and the product is named ODA-DAFPD / 6FDA copolymer polyimide, wherein ODA, DAFPD, and 6FDA are the English abbreviations of the monomers of the copolymer polyimide, and represent 4,4'-diaminodiphenyl ether, 6-(2,3,5,6-tetrafluoro-4-vinylphenoxy)pyrimidine-2,4-diamine, and 4,4'-(hexafluoroisopropylene) diphthalic anhydride, respectively.

[0018] The invention discloses a method for preparing a heat-crosslinked high-temperature resistant polyimide. The method comprises the following steps: in a polar solvent, two diamine monomers, 4,4'-diaminodiphenyl ether and 6-(2,3,5,6-tetrafluoro-4-vinylphenoxy)pyrimidine-2,4-diamine, and a dianhydride monomer, 4,4'-(hexafluoroisopropylene)diphthalic anhydride, are copolymerized, and then acetic anhydride is used as a dehydrating agent and triethylamine is used as a catalyst for a dehydration cyclization reaction. The molar feed amounts of the dehydrating agent, acetic anhydride, and the catalyst, triethylamine, are 15:15:10:m:n for acetic anhydride:triethylamine:4,4'-(hexafluoroisopropylene)diphthalic anhydride:4,4'-diaminodiphenyl ether and 6-(2,3,5,6-tetrafluoro-4-vinylphenoxy)pyrimidine-2,4-diamine; wherein n is 0.5-1.5, and m+n=10.

[0019] The selected polar solvent is N, N-dimethylformamide, N, N-dimethylacetamide or N-methylpyrrolidone; the amount of the polar solvent is 5 to 10 times the total mass of the diamine and dianhydride monomers.

[0020] The polymerization reaction temperature is 20-30°C; the reaction time is 18-36h; the dehydration cyclization temperature is 25-100°C, and the reaction time is 4-8h.

[0021] The present invention uses a general polyimide film-forming method as follows: the obtained heat-crosslinked high-temperature resistant polyimide material is dissolved in the above-mentioned same polar solvent, coated on a quartz glass plate, and placed in a tubular furnace under a nitrogen atmosphere for heat treatment to obtain a heat-crosslinked high-temperature resistant polyimide film material.

[0022] The experimental conditions for heat treatment are 260-300°C and reaction time is 2-6h.

[0023] The heat-crosslinked high-temperature resistant polyimide film material prepared by the present invention has a temperature of 5% mass loss at high temperature of 500-524° C. obtained by a thermogravimetric analyzer, and a glass transition temperature of 274-295° C. obtained by a differential scanning calorimeter test, which can basically meet the technical requirements of flexible substrates for high-temperature resistant PI materials.

[0024] The specific instructions are as follows:

[0025] The first aspect of the present invention provides a novel diamine monomer structure 6-(2,3,5,6-tetrafluoro-4-vinylphenoxy)pyrimidine-2,4-diamine (defined as DAFPD in English), characterized by having a tetrafluorostyrene crosslinkable group.

[0026] The second aspect of the present invention provides a method for preparing the novel diamine monomer DAFPD as described in the first aspect of the present invention, the method comprising the following steps:

[0027] Under nitrogen protection and in the presence of a catalyst and a polar solvent, 2,6-diaminopyrimidine-4-ol and 2,3,4,5,6-pentafluorostyrene undergo a nucleophilic substitution reaction, and then the novel diamine monomer DAFPD is obtained after filtration, extraction, reduced pressure distillation to remove the solvent, silica gel column chromatography purification, and drying.

[0028] The catalysts used in the above steps are calcium hydride and cesium fluoride; the molar feed amount of the raw materials is 6-(2,3,5,6-tetrafluoro-4-vinylphenoxy)pyrimidine-2,4-diamine: (calcium hydride): (cesium fluoride): (2,3,4,5,6-pentafluorostyrene) = 1:2:0.1:1.2 to 1:2:0.3:2, preferably 1:2:0.1:1.2.

[0029] The polar solvent used in the above steps is N,N-dimethylacetamide (DMAc), and the amount of solvent added is 5 to 10 times the total mass of the feed, preferably 7 times;

[0030] The nucleophilic substitution reaction in the above step is carried out at 75-100°C for 18-36 hours, preferably at 85°C for 24 hours;

[0031] The instrument used for the filtration described in the above steps is a G6 sand core funnel;

[0032] The solvent used for the silica gel column chromatography purification described in the above steps is an ethyl acetate / petroleum ether mixed solvent. The specific steps are to perform gradient elution when passing through the column, and to detect the effluent every 50 mL by HPLC. Only the effluent with a purity higher than 99% is combined. The test conditions of HPLC are: UV detector wavelength 254 nm, methanol as mobile phase, column temperature 25° C., flow rate 1.0 mL / min.

[0033] The third aspect of the present invention provides a series of number average molecular weight range of 4.5 ~ 6.2 × 10 4 The heat-crosslinked high-temperature resistant polyimide has the following chemical structure:

[0034]

[0035] The fourth aspect of the present invention provides a method for preparing the thermally cross-linked polyimide as described in the third aspect of the present invention, which is obtained by the following steps: first, in a polar solvent, a new diamine monomer DAFPD and a commercial diamine 4,4'-diaminodiphenyl ether (ODA) are copolymerized with a commercial dianhydride monomer 4,4'-(hexafluoroisopropylene) diphthalic anhydride (6FDA), and a polyimide material is obtained through an imidization reaction.

[0036] The polar solvent selected for the copolymerization reaction is N,N-dimethylacetamide (DMAc), N,N-dimethylformamide (DMF) or N-methylpyrrolidone (NMP).

[0037] The amount of the polar solvent used in the copolymerization reaction is 5 to 10 times the total mass of the diamine and dianhydride monomers, preferably 7 times.

[0038] The copolymerization reaction temperature is 20-30°C, preferably 25°C, and the copolymerization reaction time is 18-36h, preferably 24h.

[0039] The dehydrating agent and catalyst used in the dehydration cyclization process are acetic anhydride and triethylamine respectively, and the molar feed amounts are acetic anhydride: triethylamine: 6FDA: ODA: DAFPD of 10-50: 5-50: 10: m: n; wherein n is 0.5-1.5, and m+n=10; preferably 15: 15: 10: 9.5: 0.5.

[0040] The experimental conditions for the dehydration cyclization are 25-100° C. for 4-8 h, preferably 60° C. for 6 h.

[0041] The fifth aspect of the present invention provides a method for forming a heat-crosslinked high-temperature resistant polyimide film, wherein the heat-crosslinked polyimide as described in the fourth aspect of the present invention is dissolved in the same polar solvent, coated on a quartz glass plate, and placed in a tubular furnace under a nitrogen atmosphere for heat treatment to obtain a heat-crosslinked high-temperature resistant polyimide film material.

[0042] The experimental conditions of the heat treatment are 260-300° C. and reaction time of 2-6 hours, preferably 260° C. and reaction time of 6 hours.

[0043] The novel diamine monomer DAFPD of the present invention can also be used in the following aspects:

[0044] (1) As the third monomer, it is added into the reaction system of aromatic diamine and aromatic dianhydride to prepare modified high-transparent polyimide;

[0045] (2) Used as raw materials for the preparation of new polymer intermediates.

[0046] Effect description of the present invention:

[0047] (1) A new diamine monomer structure 6-(2,3,5,6-tetrafluoro-4-vinylphenoxy)pyrimidine-2,4-diamine was designed and successfully synthesized. The monomer is characterized by having a tetrafluorostyrene cross-linkable group. Polyimide is prepared by copolymerizing this monomer with other diamine monomers and dianhydride monomers. The tetrafluorostyrene structure is introduced into the main chain of the polyimide, and a thermally cross-linked high-temperature resistant polyimide film is prepared. The thermal cross-linking of the vinyl group and the large-volume side groups give the polyimide the advantages of high temperature resistance and improved mechanical properties.

[0048] (2) In the field of flexible substrate applications, PI materials are one of the development targets of flexible substrate technology. The thermal properties of commercially available PI films cannot meet the performance requirements of flexible OLED substrates. The polyimide film material prepared by the present invention has a mass loss temperature of 5% at high temperature of 500-524°C obtained by a thermogravimetric analyzer, and a glass transition temperature of 274-295°C obtained by a differential scanning calorimeter test, which can basically meet the technical requirements of flexible substrates for high temperature resistant PI materials.

[0049] (3) The novel diamine monomer synthesis method provided by the present invention is relatively easy, and the raw materials are easily available; the synthesis yield of polyimide is high, exceeding 90%, the preparation method is simple to operate, and the thermal crosslinking form used does not require complicated pressure equipment and dark-colored chemical crosslinking agents, etc., which will not limit the application scope of PI in flexible displays. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 New diamine DAFPD 1 H NMR spectrum

[0051] Figure 2 FTIR spectrum of the new diamine DAFPD

[0052] Figure 3 FTIR spectrum of thermally cross-linked polyimide film material (n=0.5~1.5)

[0053] Figure 4 TGA curve of thermally cross-linked polyimide film material (n=0.5)

[0054] Figure 5 TGA curve of thermally cross-linked polyimide film material (n=1.0)

[0055] Figure 6 TGA curve of thermally cross-linked polyimide film material (n=1.5)

[0056] Figure 7 DSC curve of thermally cross-linked polyimide film material (n=0.5)

[0057] Figure 8 DSC curve of thermally cross-linked polyimide film material (n=1.0)

[0058] Fig. 9 DSC curve of thermally cross-linked polyimide film material (n=1.5) DETAILED DESCRIPTION

[0059] After long and in-depth research, the inventors have designed a new type of diamine monomer DAFPD, through which a new method for preparing thermally cross-linked high-temperature resistant polyimide film materials can be developed. The obtained thermally cross-linked polyimide film material has a mass loss temperature of 500-524°C at high temperature, a glass transition temperature of 274-295°C, and good mechanical properties and flexibility, which can basically meet the technical requirements of flexible substrates for high-temperature resistant PI materials.

[0060] Example 1 Novel diamine monomer DAFPD.

[0061] Vacuum and pass nitrogen three times to exhaust air and moisture. Add 2.19g (17.40mmol) of 2,6-diaminopyrimidine-4-ol, 1.47g (34.80mmol) of calcium hydride, 0.27g (1.74mmol) of cesium fluoride, 4.08g (21.00mmol) of 2,3,4,5,6-pentafluorostyrene, and 80mL of DMAc as solvent in a 100mL three-necked flask. Stir the mixture under nitrogen atmosphere, heat to 85℃ and reflux for reaction for 24h. After the reaction is completed, cool naturally to room temperature, filter out the remaining inorganic matter through a G6 sand core funnel, pour the filtrate into deionized water for precipitation, and wash the precipitate with deionized water. The product was extracted into an ether solution with ether, the ether was dried by rotary evaporation, and then purified by silica gel column chromatography (developing solvent: ethyl acetate / petroleum ether, gradient elution), and finally a light yellow solid was obtained with a yield of 42% and a purity of 99.65% (HPLC: UV detector wavelength 254 nm, column temperature 25°C, mobile phase: pure methanol).

[0062] The product H NMR spectrum is as follows Figure 1 As shown, the infrared absorption spectrum is as follows Figure 2 shown.

[0063] 1 H NMR (DMSO-D6, ppm): δ = 6.71 (dd, J = 17.9, 11.9Hz, 1H), 6.47 (s, 2H), 6.12 (s, 2H), 6.06 (d, J = 18.0Hz, 1H), 5.83 (d, J = 11.8Hz, 1H), 5.38 (d, J = 0.9Hz, 1H).

[0064] Example 2 Novel diamine monomer DAFPD.

[0065] Vacuum and pass nitrogen three times to exhaust air and moisture. Add 2.19g (17.40mmol) of 2,6-diaminopyrimidine-4-ol, 1.47g (34.80mmol) of calcium hydride, 0.54g (3.48mmol) of cesium fluoride, 5.40g (27.80mmol) of 2,3,4,5,6-pentafluorostyrene, and 40mL of DMAc as solvent in a 100mL three-necked flask. Stir the mixture under nitrogen atmosphere, heat to 75℃ and reflux for reaction for 36h. After the reaction is completed, cool naturally to room temperature, filter out the remaining inorganic matter through a G6 sand core funnel, pour the filtrate into deionized water for precipitation, and wash the precipitate with deionized water. The product was extracted into an ether solution with ether, the ether was dried by rotary evaporation, and then purified by silica gel column chromatography (developing solvent: ethyl acetate / petroleum ether, gradient elution), and finally a light yellow solid was obtained with a yield of 41% and a purity of 99.17% (HPLC: UV detector wavelength 254 nm, column temperature 25°C, mobile phase: pure methanol).

[0066] Example 3 Novel diamine monomer DAFPD.

[0067] Vacuum and pass nitrogen three times to exhaust air and moisture. Add 2.19g (17.40mmol) of 2,6-diaminopyrimidine-4-ol, 1.47g (34.80mmol) of calcium hydride, 0.81g (5.22mmol) of cesium fluoride, 6.75g (34.80mmol) of 2,3,4,5,6-pentafluorostyrene, and 60mL of DMAc as solvent in a 100mL three-necked flask. Stir the mixture under nitrogen atmosphere, heat to 100℃ and reflux for reaction for 18h. After the reaction is completed, cool naturally to room temperature, filter out the remaining inorganic matter through a G6 sand core funnel, pour the filtrate into deionized water for precipitation, and wash the precipitate with deionized water. The product was extracted into an ether solution with ether, the ether was dried by rotary evaporation, and then purified by silica gel column chromatography (developing solvent: ethyl acetate / petroleum ether, gradient elution), and finally a light yellow solid was obtained with a yield of 40% and a purity of 98.97% (HPLC: UV detector wavelength 254nm, column temperature 25°C, mobile phase: pure methanol).

[0068] Example 4: Thermally cross-linked polyimide material (n=0.5).

[0069] A 100mL Schlenk reaction bottle equipped with a nitrogen inlet and outlet and magnetic stirring was placed in a 25°C constant temperature water bath, and vacuum and nitrogen were repeatedly pumped three times to exhaust moisture and air, and diamine monomer ODA (0.95g, 4.50mmol) and new diamine monomer DAFPD (0.075g, 0.50mmol) and 23mL DMAc solvent were added, and after stirring until completely dissolved, dianhydride 6FDA (2.22g, 5.00mmol) was added, and the reaction mixture was stirred at 25°C for 24h to obtain a polyamic acid (PAA) solution. Then, 0.76mL (7.5mmol) of triethylamine and 0.76mL (7.5mmol) of acetic anhydride were added to the PAA solution as a catalyst and a dehydrating agent, respectively, and the temperature was raised to 60°C and maintained for 6h for dehydration cyclization reaction to obtain a viscous polyimide solution. The obtained polymer solution was poured into a mixed solution of anhydrous methanol: water = 1:1 (volume ratio) for precipitation and thorough washing, then soaked in anhydrous methanol for 12 hours, and dried in a vacuum drying oven at 120°C for 24 hours to obtain a slightly yellow polyimide material with a yield of 99.5%. The structural formula is as follows:

[0070]

[0071] Example 5: Thermally cross-linked polyimide material (n=0.5).

[0072] A 100mL Schlenk reaction bottle equipped with a nitrogen inlet and outlet and magnetic stirring was placed in a 20°C constant temperature water bath, and vacuum and nitrogen were repeatedly pumped three times to exhaust moisture and air, and diamine monomer ODA (0.95g, 4.50mmol) and new diamine monomer DAFPD (0.075g, 0.50mmol) and 16mL NMP solvent were added, and after stirring until completely dissolved, dianhydride 6FDA (2.22g, 5.00mmol) was added, and the reaction mixture was stirred at 20°C for 36h to obtain a polyamic acid (PAA) solution. Then, 0.25mL (2.5mmol) of triethylamine and 0.51mL (5.0mmol) of acetic anhydride were added to the PAA solution as a catalyst and a dehydrating agent, respectively, and the temperature was raised to 100°C and maintained for 4h for dehydration cyclization reaction to obtain a viscous polyimide solution. The obtained polymer solution was poured into a mixed solution of anhydrous methanol: water = 1:1 (volume ratio) for precipitation and thorough washing, and then soaked in anhydrous methanol for 12 hours, and then dried in a vacuum drying oven at 120° C. for 24 hours to obtain a light yellow polyimide material with a yield of 99.1%.

[0073] Example 6: Thermally cross-linked polyimide material (n=0.5).

[0074] A 100mL Schlenk reaction bottle equipped with a nitrogen inlet and outlet and magnetic stirring was placed in a 30°C constant temperature water bath, and vacuum and nitrogen were repeatedly pumped three times to exhaust moisture and air, and diamine monomer ODA (0.95g, 4.50mmol) and new diamine monomer DAFPD (0.075g, 0.50mmol) and 32mL DMF solvent were added, and after stirring until completely dissolved, dianhydride 6FDA (2.22g, 5.00mmol) was added, and the reaction mixture was stirred at 30°C for 18h to obtain a polyamic acid (PAA) solution. Then, triethylamine 2.5mL (25mmol) and acetic anhydride 2.5mL (25mmol) were added to the PAA solution as catalysts and dehydrating agents, respectively, and the temperature was raised to 25°C and maintained for 8h for dehydration cyclization reaction to obtain a viscous polyimide solution. The obtained polymer solution was poured into a mixed solution of anhydrous methanol: water = 1:1 (volume ratio) for precipitation and thorough washing, and then soaked in anhydrous methanol for 12 hours, and then dried in a vacuum drying oven at 120° C. for 24 hours to obtain a light yellow polyimide material with a yield of 99.2%.

[0075] Example 7: Thermally cross-linked polyimide material (n=1.0).

[0076] A 100mL Schlenk reaction bottle equipped with a nitrogen inlet and outlet and magnetic stirring was placed in a 25°C constant temperature water bath, and vacuum and nitrogen were repeatedly pumped three times to exhaust moisture and air, and diamine monomer ODA (0.90g, 4.00mmol) and new diamine monomer DAFPD (0.09g, 0.50mmol) and 23mL DMAc solvent were added, and after stirring until completely dissolved, dianhydride 6FDA (2.22g, 5.00mmol) was added, and the reaction mixture was stirred at 25°C for 24h to obtain a polyamic acid (PAA) solution. Then, 0.76mL (7.5mmol) of triethylamine and 0.76mL (7.5mmol) of acetic anhydride were added to the PAA solution as catalysts and dehydrating agents, respectively, and the temperature was raised to 60°C and maintained for 6h for dehydration cyclization reaction to obtain a viscous polyimide solution. The obtained polymer solution was poured into a mixed solution of anhydrous methanol: water = 1:1 (volume ratio) for precipitation and thorough washing, then soaked in anhydrous methanol for 12 hours, and dried in a vacuum drying oven at 120°C for 24 hours to obtain a slightly yellow polyimide material with a yield of 99.4%. The structural formula is as follows:

[0077]

[0078] Example 8: Thermally cross-linked polyimide material (n=1.0).

[0079] A 100mL Schlenk reaction bottle equipped with a nitrogen inlet and outlet and magnetic stirring was placed in a 20°C constant temperature water bath, and vacuum and nitrogen were repeatedly pumped three times to exhaust moisture and air, and diamine monomer ODA (0.90g, 4.00mmol) and new diamine monomer DAFPD (0.09g, 0.50mmol) and 16mL NMP solvent were added, and after stirring until completely dissolved, dianhydride 6FDA (2.22g, 5.00mmol) was added, and the reaction mixture was stirred at 20°C for 36h to obtain a polyamic acid (PAA) solution. Then, 0.25mL (2.5mmol) of triethylamine and 0.51mL (5.0mmol) of acetic anhydride were added to the PAA solution as a catalyst and a dehydrating agent, respectively, and the temperature was raised to 100°C and maintained for 4h for dehydration cyclization reaction to obtain a viscous polyimide solution. The obtained polymer solution was poured into a mixed solution of anhydrous methanol: water = 1:1 (volume ratio) to precipitate and fully wash, then soaked in anhydrous methanol for 12 hours, and dried in a vacuum drying oven at 120° C. for 24 hours to obtain a slightly yellow polyimide material with a yield of 98.4%.

[0080] Example 9: Thermally cross-linked polyimide material (n=1.0).

[0081] A 100mL Schlenk reaction bottle equipped with a nitrogen inlet and outlet and magnetic stirring was placed in a 30°C constant temperature water bath, and vacuum and nitrogen were repeatedly pumped three times to exhaust moisture and air, and diamine monomer ODA (0.90g, 4.00mmol) and new diamine monomer DAFPD (0.09g, 0.50mmol) and 32mL DMF solvent were added, and after stirring until completely dissolved, dianhydride 6FDA (2.22g, 5.00mmol) was added, and the reaction mixture was stirred at 30°C for 18h to obtain a polyamic acid (PAA) solution. Then, triethylamine 2.5mL (25mmol) and acetic anhydride 2.5mL (25mmol) were added to the PAA solution as catalysts and dehydrating agents, respectively, and the temperature was raised to 25°C and maintained for 8h for dehydration cyclization reaction to obtain a viscous polyimide solution. The obtained polymer solution was poured into a mixed solution of anhydrous methanol: water = 1:1 (volume ratio) to precipitate and fully wash, then soaked in anhydrous methanol for 12 hours, and dried in a vacuum drying oven at 120° C. for 24 hours to obtain a slightly yellow polyimide material with a yield of 95.4%.

[0082] Example 10: Thermally cross-linked polyimide material (n=1.5).

[0083] A 100mL Schlenk reaction bottle equipped with a nitrogen inlet and outlet and magnetic stirring was placed in a 25°C constant temperature water bath, and vacuum and nitrogen were repeatedly drawn three times to exhaust moisture and air, and diamine monomer ODA (0.85g, 4.00mmol) and new diamine monomer DAFPD (0.105g, 0.50mmol) and 23mL DMAc solvent were added, and after stirring until completely dissolved, dianhydride 6FDA (2.22g, 5.00mmol) was added, and the reaction mixture was stirred at 25°C for 24h to obtain a polyamic acid (PAA) solution. Then, 0.76mL (7.5mmol) of triethylamine and 0.76mL (7.5mmol) of acetic anhydride were added to the PAA solution as catalysts and dehydrating agents, respectively, and the temperature was raised to 60°C and maintained for 6h for dehydration cyclization reaction to obtain a viscous polyimide solution. The obtained polymer solution was poured into a mixed solution of anhydrous methanol: water = 1:1 (volume ratio) for precipitation and thorough washing, then soaked in anhydrous methanol for 12 hours, and then placed in a vacuum drying oven at 120°C for 24 hours to obtain a slightly yellow polyimide material with a yield of 98.4%. The structural formula is as follows:

[0084]

[0085] Example 11: Thermally cross-linked polyimide material (n=1.5).

[0086] A 100mL Schlenk reaction bottle equipped with a nitrogen inlet and outlet and magnetic stirring was placed in a 20°C constant temperature water bath, and vacuum and nitrogen were repeatedly pumped three times to exhaust moisture and air, and diamine monomer ODA (0.85g, 4.00mmol) and new diamine monomer DAFPD (0.105g, 0.50mmol) and 16mL NMP solvent were added, and after stirring until completely dissolved, dianhydride 6FDA (2.22g, 5.00mmol) was added, and the reaction mixture was stirred at 20°C for 36h to obtain a polyamic acid (PAA) solution. Then, 0.25mL (2.5mmol) of triethylamine and 0.51mL (5.0mmol) of acetic anhydride were added to the PAA solution as a catalyst and a dehydrating agent, respectively, and the temperature was raised to 100°C and maintained for 4h for dehydration cyclization reaction to obtain a viscous polyimide solution. The obtained polymer solution was poured into a mixed solution of anhydrous methanol: water = 1:1 (volume ratio) to precipitate and fully wash, then soaked in anhydrous methanol for 12 hours, and dried in a vacuum drying oven at 120°C for 24 hours to obtain a slightly yellow polyimide material with a yield of 97.7%.

[0087] Example 12: Thermally cross-linked polyimide material (n=1.5).

[0088] A 100mL Schlenk reaction bottle equipped with a nitrogen inlet and outlet and magnetic stirring was placed in a 30°C constant temperature water bath, and vacuum and nitrogen were repeatedly pumped three times to exhaust moisture and air, and diamine monomer ODA (0.85g, 4.00mmol) and new diamine monomer DAFPD (0.105g, 0.50mmol) and 32mL DMF solvent were added, and after stirring until completely dissolved, dianhydride 6FDA (2.22g, 5.00mmol) was added, and the reaction mixture was stirred at 30°C for 18h to obtain a polyamic acid (PAA) solution. Then, triethylamine 2.5mL (25mmol) and acetic anhydride 2.5mL (25mmol) were added to the PAA solution as catalysts and dehydrating agents, respectively, and the temperature was raised to 25°C and maintained for 8h for dehydration cyclization reaction to obtain a viscous polyimide solution. The obtained polymer solution was poured into a mixed solution of anhydrous methanol: water = 1:1 (volume ratio) to precipitate and fully wash, then soaked in anhydrous methanol for 12 hours, and dried in a vacuum drying oven at 120°C for 24 hours to obtain a slightly yellow polyimide material with a yield of 96.9%.

[0089] Example 13: Thermally cross-linked polyimide film material (n=0.5).

[0090] 0.5 g of polyimide material was dissolved in 5.0 mL of DMF solvent and magnetically stirred overnight. After complete dissolution, the material was centrifuged at 1000 r / min for 10 min to eliminate bubbles. The polyimide solution was then coated on a 50 mm × 50 mm quartz plate and cast into a film. The film was placed in a vacuum drying oven and programmed to heat (50°C, 3 h; 80°C, 3 h; 100°C, 3 h; 120°C, 3 h; 140°C, 6 h) to remove the solvent. The film was then placed in a tubular furnace under a nitrogen atmosphere and heat treated at 300°C for 2 h to obtain a thermally cross-linked polyimide film material with a gel fraction of 68.1%.

[0091] Example 14: Thermally cross-linked polyimide film material (n=0.5).

[0092] 0.5 g of polyimide material was dissolved in 5.0 mL of NMP solvent and magnetically stirred overnight. After complete dissolution, the mixture was centrifuged at 1000 r / min for 10 min to eliminate bubbles. The polyimide solution was then coated on a 50 mm × 50 mm quartz plate and cast into a film. The film was placed in a vacuum drying oven and subjected to programmed temperature rise (50°C, 3 h; 80°C, 3 h; 100°C, 3 h; 120°C, 3 h; 140°C, 6 h) to remove the solvent. The film was then placed in a tubular furnace under a nitrogen atmosphere and heat treated at 280°C for 4 h to obtain a thermally cross-linked polyimide film material with a gel fraction of 71.7%.

[0093] Example 15: Thermally cross-linked polyimide film material (n=0.5).

[0094] 0.5 g of polyimide material was dissolved in 5.0 mL of DMAc solvent and magnetically stirred overnight. After complete dissolution, the film was centrifuged at 1000 r / min in a centrifuge for 10 min to eliminate bubbles. The polyimide solution was then coated on a 50 mm × 50 mm quartz plate and cast into a film. The film was placed in a vacuum drying oven and programmed to heat (50°C, 3 h; 80°C, 3 h; 100°C, 3 h; 120°C, 3 h; 140°C, 6 h) to remove the solvent. The film was then placed in a tubular furnace under a nitrogen atmosphere and heat treated at 260°C for 6 h to obtain a thermally cross-linked polyimide film material with a gel fraction of 75.6%.

[0095] Example 16 Thermally cross-linked polyimide film material (n=1.0).

[0096] 0.5 g of polyimide material was dissolved in 5.0 mL of DMF solvent and magnetically stirred overnight. After complete dissolution, the material was centrifuged at 1000 r / min for 10 min to eliminate bubbles. The polyimide solution was then coated on a 50 mm × 50 mm quartz plate and cast into a film. The film was placed in a vacuum drying oven and programmed to heat (50°C, 3 h; 80°C, 3 h; 100°C, 3 h; 120°C, 3 h; 140°C, 6 h) to remove the solvent. The film was then placed in a tubular furnace under a nitrogen atmosphere and heat treated at 300°C for 2 h to obtain a thermally cross-linked polyimide film material with a gel fraction of 69.4%.

[0097] Example 17: Thermally cross-linked polyimide film material (n=1.0).

[0098] 0.5 g of polyimide material was dissolved in 5.0 mL of NMP solvent and magnetically stirred overnight. After complete dissolution, the mixture was centrifuged at 1000 r / min for 10 min to eliminate bubbles. The polyimide solution was then coated on a 50 mm × 50 mm quartz plate and cast into a film. The film was placed in a vacuum drying oven and programmed to heat (50°C, 3 h; 80°C, 3 h; 100°C, 3 h; 120°C, 3 h; 140°C, 6 h) to remove the solvent. The film was then placed in a tubular furnace under a nitrogen atmosphere and heat treated at 280°C for 4 h to obtain a thermally cross-linked polyimide film material with a gel fraction of 78.3%.

[0099] Example 18 Thermally cross-linked polyimide film material (n=1.0).

[0100] 0.5 g of polyimide material was dissolved in 5.0 mL of DMAc solvent and magnetically stirred overnight. After complete dissolution, the film was centrifuged at 1000 r / min in a centrifuge for 10 min to eliminate bubbles. The polyimide solution was then coated on a 50 mm × 50 mm quartz plate and cast into a film. The film was placed in a vacuum drying oven and programmed to heat (50°C, 3 h; 80°C, 3 h; 100°C, 3 h; 120°C, 3 h; 140°C, 6 h) to remove the solvent. The film was then placed in a tubular furnace under a nitrogen atmosphere and heat treated at 260°C for 6 h to obtain a thermally cross-linked polyimide film material with a gel fraction of 88.1%.

[0101] Example 19: Thermally cross-linked polyimide film material (n=1.5).

[0102] 0.5 g of polyimide material was dissolved in 5.0 mL of DMF solvent and magnetically stirred overnight. After complete dissolution, the material was centrifuged at 1000 r / min for 10 min to eliminate bubbles. The polyimide solution was then coated on a 50 mm × 50 mm quartz plate and cast into a film. The film was placed in a vacuum drying oven and programmed to heat (50°C, 3 h; 80°C, 3 h; 100°C, 3 h; 120°C, 3 h; 140°C, 6 h) to remove the solvent. The film was then placed in a tubular furnace under a nitrogen atmosphere and heat treated at 300°C for 2 h to obtain a thermally cross-linked polyimide film material with a gel fraction of 71.1%.

[0103] Example 20: Thermally cross-linked polyimide film material (n=1.5).

[0104] 0.5 g of polyimide material was dissolved in 5.0 mL of NMP solvent with magnetic stirring overnight. After complete dissolution, the mixture was centrifuged at 1000 r / min for 10 min to eliminate bubbles. The polyimide solution was then coated on a 50 mm × 50 mm quartz plate and cast into a film. The film was placed in a vacuum drying oven and subjected to programmed temperature rise (50°C, 3 h; 80°C, 3 h; 100°C, 3 h; 120°C, 3 h; 140°C, 6 h) to remove the solvent. The film was then placed in a tubular furnace under a nitrogen atmosphere and heat treated at 280°C for 4 h to obtain a thermally cross-linked polyimide film material with a gel fraction of 85.2%.

[0105] Example 21 Thermally cross-linked polyimide film material (n=1.5).

[0106] 0.5 g of polyimide material was dissolved in 5.0 mL of DMAc solvent and magnetically stirred overnight. After complete dissolution, the film was centrifuged at 1000 r / min in a centrifuge for 10 min to eliminate bubbles. The polyimide solution was then coated on a 50 mm × 50 mm quartz plate and cast into a film. The film was placed in a vacuum drying oven and programmed to heat (50°C, 3 h; 80°C, 3 h; 100°C, 3 h; 120°C, 3 h; 140°C, 6 h) to remove the solvent. The film was then placed in a tubular furnace under a nitrogen atmosphere and heat treated at 260°C for 6 h to obtain a thermally cross-linked polyimide film material with a gel fraction of 90.5%.

[0107] The infrared absorption spectrum of thin film material (n = 0.5 ~ 1.5) is as follows Figure 3 shown.

[0108] Example 22 Molecular weight test of thermally cross-linked polyimide material.

[0109] Gel permeation chromatography (GPC) data of thermally cross-linked polyimide (using chromatographically pure tetrahydrofuran as the mobile phase and polystyrene as the standard for molar mass calibration).

[0110]

[0111] Example 23 Thermodynamic properties of thermally cross-linked polyimide film materials.

[0112] Thermogravimetric analysis TGA (test atmosphere is nitrogen, heating rate is 10°C / min, temperature range is 50-800°C). The TGA curve of the membrane material (n=0.5) is as follows: Figure 4 As shown, the TGA curve of the membrane material (n = 1.0) is as follows Figure 5 As shown, the TGA curve of the membrane material (n = 1.5) is as follows Figure 6 shown.

[0113] Differential scanning calorimetry DSC (test atmosphere is nitrogen, heating rate is 5°C / min, temperature range is 50-450°C), where the DSC curve of the membrane material (n=0.5) is as follows: Figure 7 As shown in Figure 2, the DSC curve of the membrane material (n = 1.0) is as follows Figure 8 As shown in Figure 2, the DSC curve of the membrane material (n = 1.5) is as follows Fig. 9 shown.

[0114] Static thermomechanical analysis (TMA) (test atmosphere is nitrogen, heating rate is 5°C / min, thermal expansion coefficient (CTE) value is the average coefficient of linear thermal expansion coefficient when heated to 300°C and then cooled in the temperature range of 50-150°C.

[0115] The tensile properties were tested using a universal testing machine at a tensile rate of 10 mm / min.

[0116]

[0117] The main innovative features of the present invention are:

[0118] (1) The present invention synthesizes a new type of high-purity diamine monomer DAFPD for the first time. The large-volume tetrafluorostyrene side groups in the monomer can give polyimide excellent processability and transparency. After high-temperature thermal curing, the dense three-dimensional cross-linked network structure of the thermally cross-linked polyimide film can give polyimide enhanced thermodynamic properties, making it a heat-resistant material with application potential.

[0119] (2) Excellent processing characteristics: The preparation of monomers and thermal cross-linking processes only uses simple synthesis methods and processing processes, without using heavy pressure equipment or other chemical cross-linking agents. The good solubility of the prepared polyimide means that the polymer film can be prepared at a relatively low temperature, reducing the energy consumption in the production process, and the polyimide thermal cross-linking film can resist the erosion of chemical solvents and has excellent heat resistance.

[0120] It should be understood that after reading the above teachings of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. A monomer for heat-crosslinked high-temperature resistant polyimide film material; characterized in that The diamine monomer is 6-(2,3,5,6-tetrafluoro-4-vinylphenoxy)pyrimidine-2,4-diamine, and its structural formula is as follows:

2. The method for preparing a monomer for a heat-crosslinked high-temperature resistant polyimide film material according to claim 1, characterized in that: Under nitrogen protection and in the presence of a catalyst and a polar solvent, 2,6-diaminopyrimidine-4-ol and 2,3,4,5,6-pentafluorostyrene undergo a nucleophilic substitution reaction, and then the diamine monomer 6-(2,3,5,6-tetrafluoro-4-vinylphenoxy)pyrimidine-2,4-diamine is obtained after filtration, extraction, reduced pressure distillation to remove the solvent, silica gel column chromatography purification, and drying.

3. The method for preparing a monomer for a heat-crosslinked high-temperature resistant polyimide film material according to claim 2, characterized in that: The catalysts used are calcium hydride and cesium fluoride; the molar feed amount of the raw materials is 6-(2,3,5,6-tetrafluoro-4-vinylphenoxy)pyrimidine-2,4-diamine:(2,3,4,5,6-pentafluorostyrene):(calcium hydride):(cesium fluoride)=1:2:0.1:1.2~1:2:0.3:

2.

4. The method for preparing a monomer for a heat-crosslinked high-temperature resistant polyimide film material according to claim 2, characterized in that: The polar solvent is N,N-dimethylacetamide, and the amount of the added solvent is 5 to 10 times the total mass of the feed.

5. The method for preparing a monomer for a heat-crosslinked high-temperature resistant polyimide film material according to claim 2, characterized in that: The nucleophilic substitution reaction occurs at 75-100°C and takes 18-36 hours.

6. The monomer for preparing the polyimide film material of heat-crosslinked high-temperature resistant polyimide film material according to claim 1, characterized in that: The polymer is obtained by copolymerization of two diamine monomers, 4,4'-diaminodiphenyl ether, 6-(2,3,5,6-tetrafluoro-4-vinylphenoxy)pyrimidine-2,4-diamine and a dianhydride monomer, 4,4'-(hexafluoroisopropylene) diphthalic anhydride; the structural formula is as follows: In the structural formula, m is the molar amount of 4,4'-diaminodiphenyl ether added during the copolymerization process, and n is the molar amount of 6-(2,3,5,6-tetrafluoro-4-vinylphenoxy)pyrimidine-2,4-diamine added during the copolymerization process, wherein n is 0.5 to 1.5; the characteristic is that m+n=10.

7. The method for preparing the polyimide film material according to claim 6, characterized in that: In a polar solvent, two diamine monomers, 4,4'-diaminodiphenyl ether and 6-(2,3,5,6-tetrafluoro-4-vinylphenoxy)pyrimidine-2,4-diamine, and a dianhydride monomer, 4,4'-(hexafluoroisopropylene) diphthalic anhydride, are copolymerized, and then a dehydration cyclization reaction is carried out using acetic anhydride as a dehydrating agent and triethylamine as a catalyst.

8. The method for preparing a polyimide film material according to claim 7, characterized in that: The molar feed amounts of the dehydrating agent acetic anhydride and the catalyst triethylamine used are acetic anhydride: triethylamine: 6FDA: ODA: DAFPD, which is 10-50: 5-50: 10: m: n; wherein n is 0.5-1.5, and m+n=10.

9. The method for preparing a polyimide film material according to claim 7, characterized in that: The polar solvent is N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone; the amount of the polar solvent is 5 to 10 times the total mass of the diamine and dianhydride monomers.

10. The method for preparing a polyimide film material according to claim 7, characterized in that: The copolymerization reaction temperature is 20-30°C, and the reaction time is 18-36h; the dehydration cyclization temperature is 25-100°C, and the reaction time is 4-8h.

Citation Information

Patent Citations

  • Crosslinkable diamine monomer, preparation method and application of crosslinkable diamine monomer in preparation of polyimide

    CN113480442A

  • Photosensitive polyimide resin composition as well as preparation method and application thereof

    CN117801596A

  • Monomer for thermal crosslinking type low-dielectric-constant polyimide film material, polyimide film material and preparation method of polyimide film material

    CN118026862A

  • Imide-based polymer colloidal dispersion for electrodeposition coating and method for producing same

    WO2018074738A1